ABDOMINOSCROTAL HYDROCELE: A SYSTEMATIC REVIEW - Utama Putri, Diana (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Introduction: In children, ASH was first described in the year 1861; however, the origin of this condition is still a topic of discussion. In most cases, juvenile children are the ones that experience the symptoms of acute ASH, which is a clinical syndrome that occurs only quite frequently. The aim: This study review about abdominoscrotal hydrocele. Methods: For this systematic review, publications that were published from 2012 to 2023 were taken into account during the search process. This was achieved through the utilization of numerous online reference sources, such as Pubmed and SagePub. The decision was made to exclude review articles, previously published works, and incomplete works. Result: We found nine studies showed the diagnosis and management patient’s with abdominoscrotal hydrocele. The dominant of the studies are case report and origin from United State. Conclusion: This condition is commonly found due to failure in embryology. An ultrasound examination can quickly show the presence of ASH, while an MRI will show which location is affected. The initial action can be monitoring, then surgery is carried out.